Brain gray matter structures associated with trait impulsivity: A systematic review and voxel‐based meta‐analysis. Issue 7 (18th February 2021) - Pan, Nanfang; Wang, Song; Zhao, Yajun; Lai, Han; Qin, Kun; Li, Jingguang; Biswal, Bharat B.; Sweeney, John A.; Gong, Qiyong
Abstract: Trait impulsivity is a multifaceted personality characteristic that contributes to maladaptive life outcomes. Although a growing body of neuroimaging studies have investigated the structural correlates of trait impulsivity, the findings remain highly inconsistent and heterogeneous. Herein, we performed a systematic review to depict an integrated delineation of gray matter (GM) substrates of trait impulsivity and a meta‐analysis to examine concurrence across previous whole‐brain voxel‐based morphometry studies. The systematic review summarized the diverse findings in GM morphometry in the past literature, and the quantitative meta‐analysis revealed impulsivity‐related volumetric GM alterations in prefrontal, temporal, and parietal cortices. In addition, we identified the modulatory effects of age and gender in impulsivity‐GM volume associations. The present study advances understanding of brain GM morphometry features underlying trait impulsivity. The findings may have practical implications in the clinical diagnosis of and intervention for impulsivity‐related disorders. Abstract : To depict an integrated delineation of grey matter substrates underlying trait impulsivity, we performed a systematic review and voxel‐based meta‐analysis to uncover volumetrically correlated regions in prefrontal, temporal, and parietal cortices. The findings may have practical implications in the clinical diagnosis of and intervention for impulsivity‐related disorders.